Lipid droplet and peroxisome biogenesis occur at the same ER subdomains - Amit S. Joshi (Nature Portfolio, 2018)
Lipid droplets (LDs) and peroxisomes are both generated by budding off the endoplasmic reticulum (ER). Here, the authors show that the yeast protein Pex30 marks ER subdomains where both LD and peroxisome biogenesis occurs, and identify MCTP2 as the putative mammalian Pex30 ortholog.